Microwave Mediated Synthesis and Analytical Method Development for the Estimation of Novel 1,4-Dihydropyridines in Bulk by RP-HPLC - Kaur, Anupreet; Kaur, Jaspreet; Bansal, Ranju (Drug Research, 2018)
The present work describes a rapid and green microwave mediated method for the synthesis and a simple and precise isocratic reverse phase HPLC method for the estimation of the biologically significant dihydropyridines. The conventional synthesis of these dihydropyridines has been previously reported from our lab. The analysis of a standard solution (1 mg/ml) was accomplished on a symmetry (4.6 mm I.D x 250 mm) C-18 column using mobile phase acetonitrile:water:triethylamine (TEA) (70:30:0.1 v/v/v) at a flow rate of 0.7 ml/min. Detection was monitored at 354 nm. The retention time for all the compounds was accomplished as less than 10 min. The compounds showed the linear response over the concentration range 10–100 µg/ml. The study is aimed to develop a rapid method for the quantification of these potent molecules. Various parameters like linearity (10–100 µg/ml), USP tailing and plate count were found to be satisfactory. The investigated parameters were studied with the freshly prepared solutions.
Keywords: Calcium channel blockers; 1,4-dihydropyridines; microwave synthesis; vasodilation; RP-HPLC